General–purpose finite–element software for fluid–structure analysis. (4th August 2014) - Kohnke, P.C.; Rajakumar, C.
An outline of the fluid–structure analysis capabilities of general–purpose finite–element software is presented. Analysis considering the influence of structure and fluid on each other is essential in applications such as a structure submerged in water, for example, a submarine or a ship. In this article, the finite–element discretisation of the governing equations of the fluid–structure problem is included. Equations are specialised to treat only the linear fluid–structure problem where the fluid is in a non–flowing state. Two types of analysis approach, namely, pressure–displacement and displacement–displacement formulation are shown. This classification is based on whether the fluid pressure or displacement is used as a dependent variable in the fluid governing equations. Example fluid–structure problems are solved using the ANSYS ® finite–element program to show the types of problems a general–purpose software is capable of analysing.